SOLUSI CERDAS UNTUK PARIWISATA HIJAU: POTENSI KECERDASAN BUATAN DI SEKTOR PARIWISATA JAWA TIMUR - Hasbi; Suci Wulandari Siregar (JURNAL KEPARIWISATAAN, 2026)
Green tourism is an important approach in maintaining environmental sustainability in the midst of the rapid development of the tourism industry, including in East Java. This research aims to explore the potential application of Artificial Intelligence (AI) in supporting the development of green tourism in major ecotourism destinations in the province. Using a descriptive-qualitative method with a literature review approach, this study examines how AI can be used in water management, waste management, transportation efficiency, and environmental quality monitoring. The results of the study show that AI can help optimize water distribution, leak detection, and control water consumption in tourist areas. In the field of waste management, AI enables the monitoring of waste volume, automatic sorting, as well as improved efficiency of the recycling process. AI can also optimize travel routes to reduce vehicle emissions and monitor air quality in real-time through integration with IoT sensors. These findings indicate that AI has great potential to support resource efficiency and environmentally sound tourism practices. This research recommends multi-sector collaboration to strengthen the implementation of technology in realizing adaptive and sustainable green tourism.